MULTITIME FLOQUET THEORY - Constantin Udrişte (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2013)
This paper is a contribution to the Floquet ideas applied for multitime overdetermined linear first order PDE dynamical systems with multi- periodic coefficients. The main results include: (1) a formula for the fundamental matrix; (2) the equivalence between a T-multi-periodic PDE system and a constant coefficient PDE system; (3) a new criteria for the controllability of overdetermined linear PDE systems.